2021
DOI: 10.48036/apims.v17i1.499
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Outcome of one Versus two Drains Insertion for Seroma Formation Following Modified Radical Mastectomy in Breast Carcinoma

Abstract: Objective: Comparative outcome of one versus two drains insertion for in the term of seroma formation following modified radical mastectomy in breast carcinoma. Methodology: This Prospective Interventional trial was conducted at Department of General Surgery, Liaquat University Hospital Hyderabad from February 2018 to January 2019.  Females with breast carcinoma admitted for modified radical mastectomy were included. Patients were divided into two groups.  Groups I underwent one drain placement and group II un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In our study mean drain volume at 7 th post operative day was 39.77 ml wit SD 14.99 ml. Shiraz Sheikh et.al in their study showed mean drain volume of 230ml 14 while Ramadanus in his study found 149 ml post MRM drain volume. 15 In our study seroma formation was observed in 14(28%) patients in electrocautery dissection and 8(16%) patients in scalpel dissection.…”
Section: Discussionmentioning
confidence: 85%
“…In our study mean drain volume at 7 th post operative day was 39.77 ml wit SD 14.99 ml. Shiraz Sheikh et.al in their study showed mean drain volume of 230ml 14 while Ramadanus in his study found 149 ml post MRM drain volume. 15 In our study seroma formation was observed in 14(28%) patients in electrocautery dissection and 8(16%) patients in scalpel dissection.…”
Section: Discussionmentioning
confidence: 85%